2016
DOI: 10.1103/physreva.94.042129
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of qubit chains by Feynman probes

Abstract: We address the characterization of qubit chains and assess the performances of local measurements compared to those provided by Feynman probes, i.e. nonlocal measurements realized by coupling a single qubit register to the chain. We show that local measurements are suitable to estimate small values of the coupling and that a Bayesian strategy may be successfully exploited to achieve optimal precision. For larger values of the coupling Bayesian local strategies do not lead to a consistent estimate. In this regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 59 publications
(76 reference statements)
0
35
0
Order By: Relevance
“…where A x,t and B x,t are the amplitudes of the states |↑ and |↓ at position x at time t, respectively. The A, B coefficients are in turn linked by the iterative relations 50,50]. In both cases the initial state of the system has been set to 1…”
Section: Evolution In Discrete-time Quantum Walkmentioning
confidence: 99%
“…where A x,t and B x,t are the amplitudes of the states |↑ and |↓ at position x at time t, respectively. The A, B coefficients are in turn linked by the iterative relations 50,50]. In both cases the initial state of the system has been set to 1…”
Section: Evolution In Discrete-time Quantum Walkmentioning
confidence: 99%
“…By free, we mean that the particle is affected only by the constraining potential that forces it to stay on the surface. The rationale behind this approach is that quantum systems are inherently sensitive to the parameters of their Hamiltonians, which may be exploited to precisely estimate the values of those parameters by performing suitable measurements on them [23][24][25][26][27][28][29][30][31][32]. This idea has been recently exploited to develop a new approach to probe macroscopic systems, based on the quantification and optimisation of the information that can be extracted by an interacting quantum probe as opposed to a classical one.…”
Section: Sensing the Curvature By A Free Particlementioning
confidence: 99%
“…An important problem in network theory is the extraction of information about the network when only a small subset of its constituents can be accessed. This has also been considered in the quantum case, and it has been shown that, provided one has suitable prior knowledge of the network, it is possible to determine several of its properties indirectly using a probe system, such as the network state 25 , temperature 26 , 27 , and coupling strengths between nodes 28 , 29 . In particular, in the case of full access, the structure of the network can in principle be determined exactly 9 , 30 .…”
Section: Introductionmentioning
confidence: 99%